Edmund Brooke Alexander papers - Alexander, Edmund Brooke, -1888.
Scrapbook of clippings pertaining to the Mexican War; and a pamphlet listing the officers under Gen. Winfield Scott's command.
Army officer.
Collection material in English.
Keywords: Mexican War, 1846-1848.; Scott, Winfield, -- 1786-1866.; Army officers